2004
DOI: 10.1097/01.ju.0000139541.68542.f6
|View full text |Cite
|
Sign up to set email alerts
|

Photoselective Vaporization of the Prostate for the Treatment of Benign Prostatic Hyperplasia: 12-Month Results From the First United States Multicenter Prospective Trial

Abstract: PVP is a unique, safe and effective outpatient modality that provides immediate symptomatic and urodynamic relief of bladder outlet obstruction secondary to BPH. Long-term followup is needed to validate further the maintenance of clinical efficacy beyond 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
3
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(145 citation statements)
references
References 11 publications
7
127
3
8
Order By: Relevance
“…Incontinence rates reported with the HoLEP range from 0.5 10 to 3%, 12 whereas incontinence rates reported with the PVP using the 80 W KTP laser range from 0 to 1.4%. 13 In terms of retrograde ejaculation, the two cases reported in this study occurred in patients with a median lobe, which was lasered in a non-contact mode. This potentially could have caused the damage to the circular muscle fibres at bladder neck.…”
Section: Discussionmentioning
confidence: 79%
“…Incontinence rates reported with the HoLEP range from 0.5 10 to 3%, 12 whereas incontinence rates reported with the PVP using the 80 W KTP laser range from 0 to 1.4%. 13 In terms of retrograde ejaculation, the two cases reported in this study occurred in patients with a median lobe, which was lasered in a non-contact mode. This potentially could have caused the damage to the circular muscle fibres at bladder neck.…”
Section: Discussionmentioning
confidence: 79%
“…Although effective, the technique can be associated with significant complications, including TUR syndrome and bleeding [3][4][5][6]. Newer technologies such as PVP offer safer and equally effective alternatives to relieve symptomatic bladder outlet obstruction [7][8][9][10][11][12][13][14][15]. Few studies however have directly examined the clinical differences between 80 W vs. 120 W PVP [17].…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been shown to result in comparatively fewer complications, e.g. reduced incidence of TUR syndrome as well as bleeding [7][8][9][10][11][12][13][14][15], Improvements to the Greenlight ™ laser system have been made over time, particularly with the introduction of the 120 W HPS system in 2006. Few however have compared the clinical performance of the newer systems with their predecessors.…”
Section: Introductionmentioning
confidence: 99%
“…In the first large, multicenter study examining the 80-W KTP laser for the treatment of BOO, Te et al [34] followed 145 patients over 1 year and found durable improvements in all urinary metrics and significant decreases in prostate volume by ultrasound. No patient required a blood transfusion, and only 3% had post-operative urinary retention.…”
Section: -W Ktp Lasermentioning
confidence: 99%